Tuberculosis tenosynovitis of the wrist: a rare case report - Rao Venkata Mahipathy, Surya Rao; Durairaj, Alagar Raja; Sundaramurthy, Narayanamurthy; Jayachandiran, Anand Prasath; Rajendran, Suresh (International Journal of Research in Medical Sciences, 2021)
Tuberculosis (TB) is a common disease of the Asian continent and has a varied presentation. Involvement of the musculoskeletal system is uncommon and presents in 10% of extrapulmonary tuberculosis. The atypical sites of tuberculous infection are the spine (51%) pelvis (12%), hip and femur (10%), knee and tibia (10%), and ribs (7%), but involvement of the wrist is rare. Tuberculosis tenosynovitis is a rare site of extra-articular TB. Delayed diagnosis and hence treatment is because it mimics many other disease processes and as a result, complications are common. Median nerve compression leading to carpal tunnel syndrome may also occur in these patients. Here, we present a case of tuberculous tenosynovitis involving the wrist flexors and the radial and ulnar bursae treated with surgery.